PENGARUH MEDIA STIK HURUF BERGAMBAR TERHADAP KEMAMPUAN PRA-MEMBACA ANAK DI TAMAN KANAK-KANAK AL-QUR’AN KASANG - Mitra Nil Ilmi; Yul Syofriend; Farida Mayar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research discusses the development of pre-reading ability in children aged 5-6 years, which is still relatively low due to limited varied and interesting media. Pictured letter stick media is a visual media that can help develop children's pre-reading abilities. This study aims to determine the effect of pictured letter stick media on pre-reading ability of children at Al-Qur'an Kasang Kindergarten. This study used quantitative research with quasi-experimental method. The research population consisted of all children at Al-Qur'an Kasang Kindergarten, with the sample being class B as the experimental group and class C as the control group, each consisting of 12 children. Data were collected through tests, observations, and documentation, then processed using t-test statistics with SPSS 25 for windows. The results showed that the use of pictured letter stick media provided a significant effect on children's pre-reading ability, evidenced by the final average post-test scores of the experimental group being higher than the control group (18.75 vs 15.41), with sig value (2-tailed) 0.001 < 0.05, so Ha was accepted and Ho was rejected. It can be concluded that pictured letter stick media has a significant effect on children's pre-reading ability.